Determining The Quality of SME Financial Reports: The Role of Accounting Understanding in Kulon Progo - Ratri Paramitalaksmi; Martinus Budiantara (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study aims to analyse the effect of education level, business owner perceptions, MSME digitalisation, and financial inclusion on the quality of MSME financial reports in Kulon Progo, as well as to examine the role of accounting knowledge as a moderating variable. The method used is quantitative with the Structural Equation Modelling–Partial Least Squares (SEM-PLS) technique. The research sample consisted of 397 MSME owners. The results show that education level, MSME digitalisation, and financial inclusion have a positive and significant effect on financial statement quality. Business owner perceptions do not have a significant effect. Accounting knowledge has a significant direct effect on financial statement quality but does not moderate the relationship between independent variables and financial statement quality. This study confirms that structural factors, particularly digitalisation and financial access, are strong determinants in driving MSME financial statement quality.